The high sensitivity of employment to agency costs: The relevance of wage rigidity - Atanas Hristov (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
This paper studies the interaction of financing constraints and labor market imperfections on the labor market and economic activity. My analysis builds on the agency cost framework of Carlstrom and Fuerst [1998. Agency costs and business cycles. Economic Theory, 12(3):583-597]. The aim of this article is to show that financing constraints can substantially amplify and propagate total factor productivity shocks in cyclical labor market dynamics. I find that under the Nash bargaining solution financing constraints increase substantially the volatility of wages, and in turn, amplification for the labor variables falls short of the observed volatilities in the data. Atop of this, the comovement between output and labor share is counterfactual. However, there is substantial scope for any type of wage rigidity and financing constraints to reinforce each other, and to generate the observed volatilities in the labor market, moreover, to produce a wide range of comovements between output and labor share.
Keywords: E24; E32; J64; G24; 330; credit and search frictions; labor market; unemployment; Verschuldungsrestriktion; Arbeitsmarkt; Lohnrigidität; Konjunktur; Arbeitslosigkeit; Volatilität; Theorie